Do positivo ao negativo : utilizando ferramentas computacionais e experimentação para a simulação de (meta)materiais refrativos - Nozela, Carina de Freitas Vellosa (2016)
This work aims at the development of physical phenomena simulations associated to mathematical modeling and experimentation. The choice of geometrical optics is due, among other reasons, to the need for raising the students’ awareness concerning this important Physics theme. Concepts related to the refraction of light were studied, from basic notions to more complex applications like the negative refraction index in metamaterials. A survey was conducted, both in literature and among students, to diagnose existing misconceptions regarding transmission, reflection and refraction of light. In view of the survey results, we analyzed some educational software available for free use (Simulations PhET - Interactive Simulations, Easy Java Simulations, Geogebra, Algodoo, Modellus and their versions and Scratch) to determine which one would be most suitable to the objectives of this work. Modellus-X was chosen because it features construction tools with various representations of the same situation, exploring or building, at the same time, equations, tables, graphics and animations, whether for exploratory or expressive modeling. The set of simulations, experiments and mathematical models presented in this paper is meant to encourage the learner to investigate diverse possibilities within Physics learning, and provide him with an enhanced teaching/learning process.